40.3: Effect of Birefringent Alignment Layer on Azimuthal Anchoring Energy Measurement - Muravsky, Alexander; Murauski, Anatoli (SID International Symposium Digest of technical papers, 2021)
Birefringent alignment layer contributes to the optics of the liquid crystal cell, which is significant for optical method of azimuthal anchoring energy measurement. We obtained analytical equation to compute the corrected value of liquid crystal twist angle subject to alignment layer retardation. The data on azimuthal anchoring energy measurements of AtA‐2 and AtA‐0042 azo‐dye photoalignment materials are obtained: above >10−4J/m2 within the wide range of exposure doses 0.04 – 5.12 J/cm2.